Increasing Understanding About the Wise Use of Social Media for Depok Communities - Heru Sugiyono; Heru Suyanto; Suprima Suprima (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The use of social media has become inevitable in modern life. Although it has many benefits, using social media can also bring risks and negative impacts, especially when not used wisely. This community service aims to increase the Depok community's understanding of using social media wisely. The method used in the implementation of community service is by conducting community service activities face to face with the people of Depok City , which is located in the Rangkap Jaya Sub-District, Pancoran Mas District - Depok City. The results of this program show a significant increase in understanding among the people of Depok. Community service program participants reported being better able to spot fake news, maintain online privacy, and interact ethically on social media. In addition, participants were also more aware of potential dangers such as online bullying and the spread of false information. This community service program has succeeded in creating positive changes in the social media usage behavior of the people of Depok. This proves the effectiveness of a community-based approach in increasing digital literacy. These findings can serve as a reference for similar efforts in other communities, promoting wiser and more responsible use of social media throughout society.